Adulteration in spices: Quality concerns and economic impact - K, Anees (Indian Horticulture, 2025)
Spice adulteration is a pervasive issue threatening food safety, trade integrity, and public health globally. This paper explores the types of adulterants, physical, chemical, biological, and microbiological, commonly found in spices, and their detection methods ranging from simple field tests to advanced AI-driven techniques. It examines the economic consequences of adulteration, including export rejections, reputational damage, and increased compliance costs. The role of international regulatory frameworks, quality standards, and block chain based traceability systems in mitigating adulteration is critically analyzed. The study underscores the urgent need for investment in quality infrastructure and international cooperation to safeguard consumer trust and ensure sustainable spice trade.